KESENYAPAN DAN KEKELIRUAN WICARA PUBLIC SPEAKING DALAM PRODUKSI KALIMAT SERTA HUBUNGANNYA DENGAN PEMAKAIAN MEMORI - Nurul Dwi Lestari (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This study aims to discuss aspects in sentence production including the phenomena of various types of silence and errors in the production of sentences (speaking) that occur in the speaker (public speaking), the factors that cause silence and errors in sentence production, the relationship between the phenomena of silence. with the memory usage process, and the things the speaker needs to pay attention to (public speaking) to avoid silences and mistakes in speaking (sentence production). This research uses a qualitative approach with descriptive analysis method. The results showed that in the speech activities carried out by public speaking, there were various forms of silence and tongue twitching caused by certain factors.